GROWTH AND DEVELOPMENT SOCIAL MEDIA STRATEGIES FOR ENTREPRENEURIAL SUCCESS: A COMPARATIVE STUDY - Irene Hasian; Friska Nurliana (INJOSEDU: International Journal of Social and Education, 2025)
This study aims to provide a comparative analysis of social media strategies employed by successful entrepreneurs, with a focus on the role of platforms such as Facebook, Instagram, and Twitter.To investigate this topic, the researchers conducted a bibliometric review of the existing literature. The review explored how entrepreneurial leaders utilize social media, with a particular emphasis on the content and tone of their online communications. The researchers conducted a comprehensive search of academic databases, including Scopus, Web of Science, and Google Scholar, to identify relevant scholarly articles and publications. . The search terms used included a combination of keywords related to social media, entrepreneurship, and business growth, such as "social media strategies", "entrepreneurial success", "small and medium enterprises", and "digital marketing". The findings from this study reveal that entrepreneurs employ a diverse range of social media strategies to drive the growth and development of their businesses. For instance, distributing information via Instagram-utilizing hashtags, captions, or tags on uploaded links assists SMEs in conducting promotions and advertisements for newly launched products. Entrepreneurs also use social media platforms to interact directly with key stakeholders, such as employees, suppliers, financiers, and partners, as well as other entrepreneurs and industry experts.